Asas-Asas Penyelesaian Perkara melalui Peradilan Adat Aceh - Muhammad Rudi Syahputra; Muksalmina; Sari Yulis (Universitas Muhammadiyah Surabaya, 2024)
Aceh customary courts have principles for resolving cases in reducing customary civil and criminal cases that occur in society, especially disputes that are not included in the formal justice system. This research aims to examine the principles underlying the resolution of cases through customary courts in Aceh, as well as how these principles are applied in the practice of resolving customary cases. By using a normative legal method, the resolution of customary cases in Aceh has its own principles that reflect the characteristics of customary law lives in Acehnese community (ureung Aceh). The principles of resolving cases through Aceh customary justice are principle of peace, justice, musyawarah and mufakat (mediation and negotiation), sincerity and willingness, fast, easy and cheap, openness, kinship, equality before the law, and guidance. The application of the principles of case resolution in the Acehnese customary justice process is a necessity. Acehnese community want cases to be resolved peacefully because this method has been a tradition passed down from generation to generation. The term for peaceful resolution of cases called suloh. Customary law does not distinguish between acts that are violations of civil law and violations of criminal law so that civil cases and criminal cases are decided simultaneously in a trial that is not separate. The use of the principle of musyawarah and mufakat in the implementation of customary justice has a very important role and determine whether or not the trial can be held.